Consideration over a Happy Organization - Gheorghina Liliana Bir̂ladeanu (Agora International Journal of Economical Sciences (AIJES), 2020)
"The happy organization" is based upon a strategy of happiness that brings real joy to the employees having the purpose to obtain productivity, innovation and profit growth. Happiness at work has not been just a simple "buzz" for a long time, it has rapidly transformed in strategies and objectives implemented in the day-to-day managerial plans of the top management in general and of the human resource manager in particular.
Keywords: 330